Circulating trimethylamine‐N‐oxide is associated with all‐cause mortality in subjects with nonalcoholic fatty liver disease. (8th June 2021) - Flores‐Guerrero, Jose L.; Post, Adrian; van Dijk, Peter R.; Connelly, Margery A.; Garcia, Erwin; Navis, Gerjan; Bakker, Stephan J. L.; Dullaart, Robin P. F.
Abstract: Background and Aims: Trimethylamine‐ N ‐oxide (TMAO), a gut microbiota‐liver metabolite, has been associated with cardiometabolic disease. However, whether TMAO is associated with nonalcoholic fatty liver disease (NAFLD) and NAFLD‐related health outcomes remains unclear. We aimed to investigate the association of TMAO with NAFLD and to assess the extent to which the association of TMAO with all‐cause mortality is dependent on the presence of NAFLD in the general population. Methods: We included 5292 participants enrolled in the Prevention of Renal and Vascular End‐stage Disease (PREVEND) cohort study. Cox proportional‐hazards regression analyses were performed to study the association of TMAO with all‐cause mortality in subjects with and without a fatty liver index (FLI) ≥60, which was used as a proxy of NAFLD. Results: During a median follow‐up of 8.2 years, 307 subjects died, of whom 133 were classified with NAFLD. TMAO was positively and independently associated with baseline FLI (Std β 0.08, 95% CI 0.05, 0.11, P  < .001). Higher TMAO was associated with increased risk of all‐cause mortality in subjects with NAFLD, in crude analysis (hazard ratio [HR] per 1 SD, 2.55, 95% CI 1.60, 4.05, P  < .001) and after full adjustment (adj HR 1.90, 95% CI 1.18, 3.04, P  = .008). Such an association was not present in subjects without NAFLD (crude HR 1.14, 95% CI 0.81, 1.71, P  = .39; adj HR 0.95, 95% CI 0.65, 1.39, P  = .78). Conclusion: This prospective study revealed that plasma concentrations of TMAO were associated with all‐cause mortality in subjects with NAFLD, independently of traditional risk factors.